From the Editors - Ilyas, Hamzah Puadi (University of Muhammadiyah Prof. DR. HAMKA, 2017)
Welcome to the July 2017 issue of Journal of ELT Research. This issue is accompanied by the spirit of post-Ramadan followed by Eid al-Fitr, two Islamic events bringing about many insightful meanings of life. The events in short bring humans closer to their Creator and be aware of their role as a creature. As a creature, we are always encouraged to learn, finding out the secret of His creation. In so doing, research is one of the ways to see the unseen phenomena. In terms of language teaching and learning, there are still many things we, ELT practitioners, do not know about. Research, even though it is simple, still can give a positive contribution. Our July 2017 issue touches a variety of issues in ELT which can give such a contribution.